COMPARISON OF THE INFLAMMATORY BOWEL DISEASES PHENOTYPE AND COURSE IN THE ELDERLY- AND EARLY-ONSET PATIENTS. (22nd January 2022) - Saberzadeh-Ardestani, Bahar; Anushiravani, Amir; Khosravi, Bardia; Vahedi, Homayoon; Malekzadeh, Masoud; Alatab, Sudabeh; Sadeghi, Anahita; Sima, Ali Reza; Malekzadeh, Reza
Abstract: BACKGROUND AND AIMS: It is unknown if clinical phenotype and course of the disease are comparable between early- and elderly-onset inflammatory bowel diseases (IBD). There is also an ongoing dispute on whether elderly-onset IBD is a separate entity. We aimed to seek differences in disease phenotype, course, complications, and treatment between early- and elderly-onset IBD patients. METHODS: This retrospective cohort study on registered IBD patients in the Iranian Registry of Crohn's and Colitis (IRCC) compared demographics, extent of ulcerative colitis (UC), Crohn's disease (CD) location and behavior, extraintestinal manifestations, disease activity during the previous six months, and two weeks, IBD-related surgery and medications between early- and elderly-onset IBD. We defined early-onset and elderly-onset IBD as 30 years or less and 60 years and above, respectively. We used univariable analysis to investigate the association between age of diagnosis and outcomes. Variables with P-value <0.1 were entered into the generalized linear model to study the relative risk of age of diagnosis adjusted for gender and disease duration for the outcomes. RESULTS: From 8911 IBD patients that were recruited in the IRCC from December 2017 till June 2021, 4503 were enrolled, including 4134 (46.4%) early-onset and 369 (4.1%) elderly-onset cases. Among them, 3596 (79.8%) had UC, and 907 (20.2%) had CD. Figure 1 shows relative risk of outcomes in patients with UC based on patients' age of diagnosis adjusted for disease duration and gender. The risk of left colitis was 1.7 times higher among elderly-onset UC patients (95%CI:1.4-2.1, P<0.001). Early-onset IBD cases had a higher prevalence of extraintestinal manifestations (p<0.001). Early-onset UC cases more often used prednisolone (p=0.031), immunomodulators (p<0.001) and anti-tumor necrosis factors (TNF) (p=0.002). Elderly-onset UC patients had 0.7 times lower risk of active disease in the past six months in comparison with elderly-onset cases (95%CI:0.5-0.9, p=0.003). Elderly-onset CD patients had 1.7 times the risk of ilium involvement (95%CI: 1.1-2.5, p=0.010), and elderly-onset CD cases had 0.2 times the risk of stricture formation compared to early cases (95%CI:0.1-0.8, p=0.028). Early-onset CD was associated with higher use of prednisolone (p=0.024), immunomodulators (p<0.001) and anti-TNF (p=0.024). Disease activity during the previous six months, two weeks and IBD-related surgery were similar between the two groups. Figure 2 demonstrates relative risk of outcomes in patients with CD based on patients' age of diagnosis adjusted for disease duration and gender. CONCLUSION: Early-onset IBD was associated with a more aggressive phenotype and higher prednisolone, immunomodulators, and anti-TNF use. There is a need for a more detailed investigation of treatment complications and surgery types in future studies.